Enhanced Adsorption of Sulfonamides by Attapulgite-Doped Biochar Prepared with Calcination - Hu, Jianqiao; Liu, Feng; Shan, Yongping; Huang, Zhenzhen; Gao, Jingqing; Jiao, Wentao (Molecules (Basel, Switzerland), 2022)
The extensive use of sulfonamides seriously threatens the safety and stability of the ecological environment. Developing green inexpensive and effective adsorbents is critically needed for the elimination of sulfonamides from wastewater. The non-modified biochar exhibited limited adsorption capacity for sulfonamides. In this study, the attapulgite-doped biochar adsorbent (ATP/BC) was produced from attapulgite and rice straw by calcination. Compared with non-modified biochar, the specific surface area of ATP/BC increased by 73.53–131.26%, and the average pore width of ATP/BC decreased 1.77–3.60 nm. The removal rates of sulfadiazine and sulfamethazine by ATP/BC were 98.63% and 98.24%, respectively, at the mass ratio of ATP to rice straw = 1:10, time = 4 h, dosage = 2 g∙L−1, pH = 5, initial concentration = 1 mg∙L−1, and temperature = 20 °C. A pseudo-second-order kinetic model (R2 = 0.99) and the Freundlich isothermal model (R2 = 0.99) well described the process of sulfonamide adsorption on ATP/BC. Thermodynamic calculations showed that the adsorption behavior of sulfonamides on the ATP/BC was an endothermic (ΔH > 0), random (ΔS > 0), spontaneous reaction (ΔG < 0) that was dominated by chemisorption (−20 kJ∙mol−1 > ΔG). The potential adsorption mechanisms include electrostatic interaction, hydrogen bonding, π–π interaction, and Lewis acid–base interactions. This study provides an optional material to treat sulfonamides in wastewater and groundwater.